2020
DOI: 10.1029/2020ea001196
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Change of Supercooled Liquid Cloud Properties by Aerosols From an Aircraft‐Based Seeding Experiment

Abstract: Cloud plays essential roles to Earth's energy balance and hydrological cycle. Its characteristics could be modified by human activities through cloud seeding. However, there is long‐lasting debate whether the cloud seeding can modify the clouds to introduce or change precipitation effectively, due to the challenge that the effect of cloud seeding is difficult to be evaluated. Using the data from a cloud seeding experiment, this study investigates the differences of cloud properties between before and after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…The dependence of cloud microphysical properties on environmental conditions can be investigated using optical probes capable of measuring DSDs (e.g., Burnet & Brenguier, 2007; Dong et al., 2020; McFarquhar, Zhang, et al., 2007; Y. Yang et al., 2019; Zhao et al., 2019) installed on aircraft. Using such in situ data, ε , r e , and LWC can be derived from the DSDs (Heymsfield & McFarquhar, 2001; Martin et al., 1994; Stephens & Platt, 1987; Zhao et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dependence of cloud microphysical properties on environmental conditions can be investigated using optical probes capable of measuring DSDs (e.g., Burnet & Brenguier, 2007; Dong et al., 2020; McFarquhar, Zhang, et al., 2007; Y. Yang et al., 2019; Zhao et al., 2019) installed on aircraft. Using such in situ data, ε , r e , and LWC can be derived from the DSDs (Heymsfield & McFarquhar, 2001; Martin et al., 1994; Stephens & Platt, 1987; Zhao et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The dependence of cloud microphysical properties on environmental conditions can be investigated using optical probes capable of measuring DSDs (e.g., Burnet & Brenguier, 2007;Dong et al, 2020;Mc-Farquhar, Zhang, et al, 2007;Y. Yang et al, 2019;Zhao et al, 2019) installed on aircraft.…”
mentioning
confidence: 99%
“…Considering the exploitation and utilization, there are much higher economic and technical costs to condense water vapour into water by direct cooling or uplift expansion cooling. However, hydrometeors can be caused to fall down to the ground to increase ground water resources by an exploitation technology with relatively lower cost (French et al, 2018;Yang et al, 2019;Dong et al, 2020). Dong et al (2021) showed robust evidences of conversion from liquid droplets to ice particles and increasing precipitation by cloud seeding.…”
Section: Introductionmentioning
confidence: 99%
“…Radar-based remote sensing provides indirect information about the characteristics of snow (Grazioli et al, 2015), and a certain canting angle assumption used in Li et al (2018) needs further evaluation. In situ instruments are useful and often necessary to better characterize clouds (Dong et al, 2020;Yang et al, 2019;Zhao et al, 2019) and precipitation (Grazioli et al, 2015;Matrosov et al, 2017). A 2-D video disdrometer (2DVD) can measure the particle shape and fall velocity near the surface (Huang et al, 2015;Kruger & Krajewski, 2002), which can be used to analyze the influence of riming on the properties of snowflakes directly.…”
mentioning
confidence: 99%